PENERAPAN TEKNOLOGI NEAR FIELD COMMUNICATION PADA SISTEM ABSENSI PERKULIAHAN - OLIVYA, MEYLANIE; PRAMINASARI, RESKI (Jurnal INSTEK (Informatika Sains dan Teknologi), 2019)
The process of recording attendance lectures is still old and takes time. Student attendance models used in the lecture process still use the old method. This method has many disadvantages including, attendance data can still be manipulated by the students concerned, manual attendance data recapitations which involve many parties and take a long time, and attendance papers that are very vulnerable to damage and may be lost. The system receives input from the Nomor Induk Pegawai (NIP) of the lecturer as a user id integrated with SIMAK. The lecturer will attend the student by using a student card, then the application will automatically process and save the data to SIMAK. The test results show that the data needed for attendance needs can be called automatically, as well as attendance data that can be stored directly in SIMAK. Keyword : NFC, SIMAK